Effect of SGLT2 inhibitors on cardiac structure and function assessed by cardiac magnetic resonance: a systematic review and meta-analysis - Isabella Leo; Nadia Salerno; Stefano Figliozzi; Angelica Cersosimo; Jessica Ielapi; Kamil Stankowski; Giandomenico Bisaccia; Santo Dellegrottaglie; Giovanni Canino; Salvatore De Rosa; Sabato Sorrentino; Chiara Bucciarelli-Ducci; et al. (Cardiovascular Diabetology)
Abstract Background and aim Sodium-glucose cotransporter-2 inhibitors (SGLT2i) improve outcomes in patients with heart failure (HF) but underlying mechanisms remain incompletely understood. Cardiac magnetic resonance (CMR) is key in evaluating cardiac structure and function, enabling accurate assessment of reverse remodeling. Aim of this systematic review and meta-analysis was to assess the effects of SGLT2i on cardiac remodeling evaluated by CMR changes. Methods We conducted a systematic review and meta-analysis of studies assessing changes in CMR parameters in patients treated with SGLT2i (PROSPERO registration: CRD42024574302). Databases were searched through April 30, 2025. Random-effects models were used to pool mean changes in left and right ventricular volumes, mass, function, stroke volume, global longitudinal strain, left atrial volume, and tissue characterization indices. Meta-regression and sensitivity analyses were performed to evaluate potential sources of heterogeneity. Results Twenty-three studies and 1008 patients were included. Treatment with SGLT2i was associated with significant reductions in left ventricular (LV) end-diastolic volume (− 7.10 mL; 95% CI: −13.01 to − 1.19, p = 0.023), left ventricular mass (− 4.24 g; 95% CI: −7.88 to − 0.60, p = 0.027) and epicardial adipose tissue (-4.94 ml; 95% CI: -9.06, -0.82, p = 0.019). A subgroup analysis in patients with reduced LV ejection fraction showed improvement in LV stroke volume. Meta-regression revealed no significant effect of age, male sex or diabetes prevalence on pooled estimates. Conclusions SGLT2i are associated with reductions in LV volumes and mass in line with an overall favorable reverse remodeling effects as assessed by CMR.